Selective and Inverse U-Shaped Curve Alteration of the Retinal Nerve in Amyotrophic Lateral Sclerosis: A Potential Mirror of the Disease - Zhang, Yixuan; Liu, Xiangyi; Fu, Jiayu; Zhang, Yuanjin; Yang, Xue; Zhang, Shuo; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2022)
Introduction: Alterations in the visual pathway involving the retina have been reported in amyotrophic lateral sclerosis(ALS) but they lack consistency and subgroup analysis. We aimed to assess the retinal nerve fiber layer(RNFL) and retinal ganglion cells(RGCs) alterations in different stages of ALS patients and their association with ALS progression parameters. Methods: The study population consisted of 70 clinically diagnosed ALS patients and 55 age, sex matched controls. All of them underwent ophthalmic assessments and optical coherence tomography imaging. Four quadrants of the peripapillary RNFL and ganglion cell/inner plexiform complex(GCIP) were observed and automatically measured. Early-stage distal motor neuron axon dysfunction in ALS was detected by compound muscle action potential(CMAP) of the distal limbs within 12 months. The ALS disease parameters included the ALSFRS-R score and the disease progression rate(ΔFS). Results: Generally compared with controls, the nasal (p=0.016) quadrant of the RNFL was thicker in ALS patients. When controlling for age and ΔFS, the RNFL(r=0.37, p=0.034) and GCIP(r=0.40, p=0.021) were significantly thickened as disease progressed within 12 months, while the RNFL declined with time after one year(r=-0.41, p=0.037). ALS patients was subclassified into thickened RNFL(T-RNFL, >95th percentile of normal), impaired RNFL(I-RNFL, <5th percentile of normal) and normal RNFL. There were significant differences in the GCIP among the three groups (p<0.001). In the T-RNFL group (n=18), the RNFL was negatively correlated with the abductor pollicis brevis-CMAP amplitude within 12 months(r=-0.56, p=0.01). Patients within 12 months in this group progressed faster than others(p=0.039). In the normal RNFL group(n=22), 13 patients were diagnosed beyond 12 months, whose ΔFS was remarkably lower(p=0.007). In I-RNFL group (n=30), the early stage patients(<12 months) had significant higher ΔFS (p=0.006). One patient was with SOD1 pathogenic variant(p.A5V). Conclusion: Alterations of retinal nerve were not consistent in ALS patients with diverse phenotypes and progression rates. Generally speaking, the RNFL thickened during the first year and then gradually declined, which is related to but preceding the thickness change of the RGCs. Patients with a significant RNFL thinning in the early stage may have a faster progression rate. The inverse U-shaped curve transformation might be in accordance with early-stage motor neuron axonopathy.